Social welfare administration as a discipline and a profession: Perspectives and prospects - Kaushik, S.L.; Sachdeva, Pradeep (1992)
After spanning the initial uncertainties of the identity of the discipline at international level, despite U.N. patronage, the authors attempt to identify its main characteristics as a profession and then take a look at its position in India. With focus on personnel administration in India, they concentrate on personnel policy aspects-i.e., recruitment, training, staff development, and motivation and morale-with particular reference to voluntary organisations. Visualising its increasing role in the developmental process, the authors suggest evolving of a partnership between government and voluntary organisations to the help its proper development as a profession. - Reproduced.
Keywords: Personnel; Social Welfare - Administration - India; Social Welfare - Administration